Using the VERT wearable device to monitor jumping loads in elite volleyball athletes - Damji, F. (University of British Columbia, 2020)
Sport is evolving into a more competitive industry, leaving athletes prone to injuries. Monitoring athletes using wearable technology provides a way to potentially manage training and competition loads with the goal of reducing injuries. One such technology is the VERT, a commercially available discrete wearable device that measures vertical displacement from the center of mass. While several studies have examined the accuracy of the VERT`s measures of jump height and jump count, landing impact has not yet been investigated. The objective of this research study was to explore the potential utility of the VERT as a load monitoring tool in elite volleyball players. This was done by (1) examining the accuracy of the VERT landing impact values in university volleyball players and (2) retrospectively analyzing a VERT data set collected over the course of a university volleyball season, documenting whether established relationships were observed between various load characteristics and knee pain. We hypothesized that the VERT landing impact values would fall within 10% of those derived from a research-grade accelerometer, the Shimmer. In the data set, we expected to see agreement with the literature in that acute:chronic workload ratio (ACR), average jump height, jump count and session rating of perceived exertion (sRPE) were positively associated with knee pain. We also expected knee pain to increase over the course of the season and for leftsides/middle blockers to report the highest pain. Methodology for the validation study included recruiting 14 players, having each perform 10 jumps while wearing both devices. For the retrospective analysis, we used linear mixed effect modelling. The results of the validation showed that VERT landing impacts were variable (limits of agreement of -84.13% and 52.37%) and had a propensity to be lower (mean bias of -15.88%) when compared to the Shimmer. In the retrospective analysis, average jump height (p=0.041) and date (p=0.032) were negatively associated with knee pain (however the associations were of small magnitude). In conclusion, the validity of the VERT device`s landing impact values are generally poor, with respect to Shimmer. The relationships in the data set were partially consistent with what previous literature has shown.